Conventional Spacers in Removable Complete Denture Prosthodontics - Muhammad Sami Khan; Muntazar Ali Mehdi; Mustafa Shahzad; Muhammad Rameez; Haroon Rashid Baloch (ziauddin University, 2024)
Complete dentures offer the replacement of all missing teeth and surrounding tissues.  Replacing the entire arch of missing teeth, the prosthesis is exclusively tissue-supported. Adapting a spacer during removable complete denture impression-making is one of the important steps. The success and failure of complete denture therapy are largely dependent upon the method by which the clinician records impressions. Many theories of impression have been proposed and the selective-pressure technique is one of the most widely used theories and has been used successfully. During the selective pressure technique, custom trays with different designs and materials spacers are used so that vulnerable tissues are relieved of undue stresses while stress-bearing areas are utilized properly. The current paper mainly describes some of the conventional wax spacers that may be used during impression making of removable complete denture prostheses.